Digital libraries and multimedia archives : 14th Italian Research Conference on Digital Libraries, IRCDL 2018, Udine, Italy, January 25-26, 2018, Proceedings /: 14th Italian Research Conference on Digital Libraries, IRCDL 2018, Udine, Italy, January 25-26, 2018, Proceedings. (2018) - Unknown
No abstract available